Internet Searches, Household Sentiment and Credit Spreads - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2019)
We use Google internet search volumes to measure households' pessimism about overall market-wide credit health in the economy, and show that this "household default sentiment" is positively correlated with the credit default swap (CDS) spread level in the market. However, while household default sentiment might drive the cost of credit to some degree, either directly or indirectly through its effect on the stock market, we find the stock market's opinion about the credit risk in the economy (default probabilities backed out from structural models) to be much more important in explaining credit spreads. The rather weak link between household sentiment and CDS spreads, meanwhile, is consistent with the almost complete absence of retail investors (households) in the institutional investor-dominated credit derivatives market. The results are essentially the same, whether we look at market-wide CDS indexes or single-name CDS contracts, and whether we exclude the financial crisis or not.
Keywords: C82; D83; G12; G14; G50; 330; sentiment; Google; internet search; households; CDS; spread; distance to default